Strategi Pemasaran Agen PT Asuransi Prudential - Bayu Prabowo; Nuri Aslami (LPPM IAI Nasional Laa Roiba Bogor, 2021)
The research is to analyze the insurance agent's marketing strategies in finding a prudential insurance account. The study uses analytical descriptive,qualitative methods, by observation, library study, documentation, data processing, data presentation, and deduction. Research indicates that the researchers' plan prudential insurance agents for obtaining such payments is by keeping up with the following cycles,planning, prospecting, approach (approaching) finding facts (facts), presentations,and closing objections/closing (closing). In order to preserve and improve on customers, insurance agents make good introductions to customers, frequent visits to customers, elaborate explanations and insights about insurance well, provide information and excellent services, always be available when customers need help with insurance, and give credit for the existing days or moments.